Social networks, psychological empowerment, and work outcomes: mediating role of psychological empowerment dimensions on the relations between social networks, job dedication, and individual creativity. (14th August 2019) - Adeel, Ahmad; Batool, Samreen; Ali, Rizwan
In this study, we linked social networks with work related outcomes. We tested dimensions of psychological empowerment as mediators between internal bonding networks, external bridging networks, job dedication and individual creativity with random coefficient modelling using Mplus 7. With a sample of 317 higher hierarchical level employees and their supervisors, it has been found, competence and self-determination dimensions of empowerment mediate the relationship between internal bonding networks and job dedication and between external bridging networks and job dedication. Meaning, competence and self-determination dimensions of psychological empowerment mediate the relationship between internal bonding networks and individual creativity and between external bridging networks and individual creativity. Contrary to our prediction, impact dimension of psychological empowerment was not significant with internal bonding networks and external bridging networks. Our findings suggest that membership of social networks enhance empowerment perceptions of employees which in turn enhance their dedication towards job and their individual level creativity.